2016
DOI: 10.3390/molecules21040423
|View full text |Cite
|
Sign up to set email alerts
|

GC×GC-TOFMS Analysis of Essential Oils Composition from Leaves, Twigs and Seeds of Cinnamomum camphora L. Presl and Their Insecticidal and Repellent Activities

Abstract: Interest in essential oils with pesticidal activity against insects and pests is growing. In this study, essential oils from different parts (leaves, twigs and seeds) of Cinnamomum camphora L. Presl were investigated for their chemical composition, and insecticidal and repellent activities against the cotton aphid. The essential oils, obtained by hydrodistillation, were analyzed by GCˆGC-TOFMS. A total of 96 components were identified in the essential oils and the main constituents found in the leaves and twig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
69
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(71 citation statements)
references
References 41 publications
2
69
0
Order By: Relevance
“…The lack of a repellent effect on M. persicae was also observed by Bruce et al () for linalol and by Hori () for α‐pinene, camphene, eucalyptol and borneol. Nevertheless, several studies demonstrated the effect of these VOCs on the behaviour of aphids and other insects (Chapman et al , ; Hori & Komatsu, ; Hori, ; Tomova et al , ; Rozman et al , ; Abdelgaleil et al , ; Halbert et al , ; Webster et al , ; Zhang et al , ; Lamy et al , ; Jiang et al , ). Such contradictions are not necessarily surprising and testify the difficulty of making comparisons without considering the experimental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of a repellent effect on M. persicae was also observed by Bruce et al () for linalol and by Hori () for α‐pinene, camphene, eucalyptol and borneol. Nevertheless, several studies demonstrated the effect of these VOCs on the behaviour of aphids and other insects (Chapman et al , ; Hori & Komatsu, ; Hori, ; Tomova et al , ; Rozman et al , ; Abdelgaleil et al , ; Halbert et al , ; Webster et al , ; Zhang et al , ; Lamy et al , ; Jiang et al , ). Such contradictions are not necessarily surprising and testify the difficulty of making comparisons without considering the experimental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…EL and EF both contained linalool (12.8%–22.9%), while safrole was retrieved only in EF. The prior paper also studied the chemical composition of the twigs and seeds of C. camphora in Jiangxi [25]. The main compounds of this essential oil were eucalyptol (17.2%), camphor (13.2%), and 3,7-dimethyl-1,3,7-octatriene (11.5%), while in seeds they were eucalyptol (20.9%), methyleugenol (20.0%), linalool (14.7%), and camphor (5.5%).…”
Section: Discussionmentioning
confidence: 99%
“…In previous works, powders and other parts of C. camphora essential oils have been evaluated for bioactivities against agricultural as well as stored product insects [12,13,14,17,18,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39]. The selected constituents also showed bioactivities and reflected the compositional complexity in bioactivity of natural mixtures [40].…”
Section: Discussionmentioning
confidence: 99%
“…The major components in the seed oil of C. amphora were eucalyptol (20.9%), methyleugenol (19.9%), linalool (14.7%) and camphor (5.5%). [47] According to Guo et al [48] , the bark oil of C. camphora from China was rich in D- In an another report from China, the main components of C. camphora leaves essential oil were D-camphor (40.5%), linalool (22.9%) and cineole (11.3%). [49] Fresh leaves of C.…”
Section: Cinnamomum Camphora (L) J Preslmentioning
confidence: 99%